Globalization Impact on the Local and Regional Development Policies: Republic of Moldova Case - Oxana Paierele (CES Working Papers, 2011)
This article focuses upon the idea of globalization and its influence on building more progressive local and regional development strategies, taking into consideration the local and regional circumstances of Republic of Moldova. An interesting task is to determine where the top-down and central control stops, as well as where local autonomy begins and the way a strong regional development of country may be built. All this due to the fact that currently a strong state, a developed and competitive one is decentralized, and should have strong local communities which grow dynamically and solve local problems quickly.
Keywords: 330; regional development; globalization; good governance; local public administration authorities; decentralization